PENGETAHUAN MENURUT HINDU DAN IMPLIKASINYA TERHADAP PENDIDIKAN MANUSIA SEUTUHNYA - SUKADI SUKADI (Purwadita : Jurnal Agama dan Budaya, 2017)
Appropriate  source,  according  to  Hindu  knowledge  includes  knowledge  of  spiritual, moral knowledge, social knowledge, knowledge of intellectual, physical and sensory knowledge. Fifth human knowledge system was developed as an integrated system. Education according to Hindu, has the obligation to develop a unified system that knowledge to themselves all students, in  order  to  allow  it  to  have  intelligence  and  consciousness  double  (multiple).  Only  with  the educational  process capable  of empowering knowledge system  as it  is,  people will  be able to grow and develop fully (fully functioning person). It is clear that education in Hindu ideology to support the establishment of a human with multiple intelligences, developed into a fully human, and develop into a human being with the acquisition of knowledge, values ??and attitudes, and skills of both aparawidya (worldly knowledge) and parawidya (noetic knowledge).